Ultrafast exciton energy transfer dynamics in the cryptophyte light-harvesting antenna phycoerythrin 566 - Guo, Na; Liang, Zidong; Guo, Xinyu; Huang, Zhencheng; Zhang, Lei; Xie, Mingyuan; Pu, Yang; Li, Wenjun; Chen, Min; Qin, Song; Zhao, Fuli (Frontiers in Plant Science, 2025)
IntroductionCryptophytes obtain energy through photosynthetic pigments and transfer it to the photosynthetic center on an ultrafast timescale. The mechanisms of such ultrafast excitation energy transfer (EET) in light-trapping complexes are a major focus of algal research. The closed-form phycoerythrin 566 (PE566) binds chemically distinct chromophores, exhibiting spectral properties that differ from those of other closed-form phycobiliproteins in cryptophytes. Elucidating the ultrafast energy transfer pathway of PE566 may provide a deeper understanding of the mechanisms involved in the initial stages of photosynthesis.MethodWe present a comprehensive description of the ultrafast energy transfer kinetics of PE566 under physiological conditions. A combined approach using ultrafast transient absorption (TA) spectroscopy and coherent modified Redfield theory (CMRT) was employed for theoretical modeling to investigate the ultrafast energy transfer between pigment molecules, including the exciton dynamics in PE566.Results and DiscussionThe results indicate that, in the PE566 dimer, the two phycoerythrobilins (PEBs) possess the highest excitation energies and act as the primary donors in the EET process. The two double-linked bilin584s serve as secondary energy transfer acceptors, exhibiting strong electronic coupling that leads to coherent delocalization of excited states. Two single-linked bilin584s and two bilin618s constitute the four lowest-energy exciton states. Ultimately, two efficient EET pathways were identified, with the lowest-energy bilin618s serving as the terminal acceptors for energy transfer in PE566. Our work clarifies the internal EET mechanism of Cryptophyta PE566, which may advance photophysical studies of phycobiliprotein systems.